The Effect of Electronic Word of Mouth (E-WOM) on Purchase Intention (Case Study on TikTok Skincare NPURE Account) in 2025 - Naela Muna Angelina; Sri Widaningsih (Eduvest - Journal of Universal Studies, 2025)
This study aims to determine the influence of electronic word of mouth (e-WOM) on consumer purchase intention for NPURE skincare products through the TikTok platform. In today's digital era, e-WOM is one of the effective marketing strategies in influencing consumer purchasing decisions, especially through social media. This study uses a quantitative approach with a simple linear regression method. The respondents in this study were 100 people who were active users of TikTok and had seen the content of NPURE products. The e-WOM variable is measured through three dimensions, namely intensity, valance of opinion, and content. Meanwhile, purchase intention is measured through four dimensions, namely transactional, referential, preferential, and exploratory interest. The results showed that electronic word of mouth was in the "quite good" category with a percentage of 67.8%, while purchase intention was in the "good" category with a percentage of 69.3%. The results of the regression analysis showed that e-WOM had a positive and significant effect on purchase intention with a significant value of <0.001, a t-value of 16.562 > t table (1.984), and a determination coefficient value of 0.737, which means that e-WOM contributed 73.7% to purchase intention. These findings reinforce the theory and previous research that the positive perceptions formed by digital reviews have an effect on consumer purchase intention. Therefore, companies need to improve their e-WOM strategy on social media to increase consumer engagement and confidence in their products.